The Meaning of Violence in The Human Centipede III: A Charles Sanders Peirce Semiotic Analysis (Oratio Directa, 2019)
The Human Centipede III portrays a prison with a high level of unrest led by a cruel prison warden. This study aims to reveal the meaning of violence in the film through Charles Sanders Peirce's semiotic analysis. It applies a descriptive qualitative approach within a constructivist paradigm. Data were obtained from video documentation and observation of violent scenes, then examined through the relationship among sign, object, and interpretant. The findings show that violence is constructed through physical, psychological, and sexual violence. Two scenes examined in detail depict hot water being poured on a prisoner and forced castration, which are interpreted as torture, domination, and the destruction of human dignity.
Keywords: Meaning; Violence; Semiotics; Film; Charles Sanders Peirce